Rancang bangun mesin pencetak bakso berbasis pneumatik - Mustika, Widya Sinta; Irwan, Purnama; Romiyadi; Ramaddan, Arya Imansyah (Jurnal Teknik Mesin Indonesia, 2024)
The conventional process of printing meatballs using hands and spoons is considered less efficient in the production process both in quality and quantity. Meanwhile, commercially available meatball printing machines are bulky and complicated to use. Therefore, the design of a meatball making machine that has smaller dimensions can be developed at a more affordable price. This research began by designing a meatball printing machine using the SolidWorks software, with a frame design made of U-profile iron, meatball containers made of stainless steel cylinders, and packaging boxes for the electrical system from the relay. In the operation of the meatball molding machine, pneumatic is used as a drive system with a time delay relay to control the time for cutting the meatball dough. The manufacture of this machine produces a pneumatic-based meatball molding machine with constant pressure, with an automatic system using a time delay relay of 2 seconds for cutting forward and 0.2 seconds for cutting backward. From testing the machine applying a mass of 2.5 kg meatball dough, 192 meatballs were obtained, with a processing time of 7 minutes 29 seconds, with a remaining dough mass of 4 ounces, and an average meatball diameter of 24.95 mm.